STATE OF FUNCTIONAL, MOTOR AND PSYCHOLOGICAL ABILITIES OF THE HIGH CLASS JUDOISTS WITH LIMITED VISUAL ABILITY DURING THE PRE-CONTEST PERIOD - Vitalii Gligor; Angela Polevaia-Secareanu; Piotr Demcenco (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this article is described the study on the functional- motor and psychological potential of high class judoka with limited visual ability.